Effect of different proportions of glycerol and D-mannitol as plasticizer on the properties of extruded corn starch - Xu, Xin; Wang, Bin; Gao, Wei; Sui, Jie; Wang, Jianfei; Cui, Bo (Frontiers in Nutrition, 2024)
In this study, thermoplastic starch (TPS) was prepared by melt extrusion process, in which glycerol and/or D-mannitol were used as plasticizers, and the effect of different glycerol/D-mannitol ratios (4:0, 3:1, 2:2, 1:3, and 0:4) on the physicochemical properties of the extruded starch samples was investigated. The short-range molecular order, crystallization, gelatinization, thermal stability, and thermal properties of the TPS samples were analyzed through attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy, X-ray diffraction (XRD), rapid visco analysis (RVA), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The results showed that the crystallinity and short-range molecular order of the TPS samples increased with increasing glycerol content.Conversely, the water absorption index (WAI) and water solubility index (WSI) of the TPS samples decreased with increasing glycerol content. In addition, the TPS samples with higher glycerol content exhibited higher gel and thermal stabilities. This study provides a theoretical basis for starch extrusion and plasticization in the preparation of TPS-based materials with specific properties.